A Survey on Product Promotion via E-commerce Platforms - Case Study in Malaysia - Alomari M.A.; Ahmed Al-Qasem Al-Hadi I.; Yusoff M.H.; Sulaiman I.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automation; Intelligent systems; Process control; Profitability; Surveys; E-commerce systems; E-commerce transactions; Efficient strategy; High speed internet; Internet users; Market penetration; Products and services; Questionnaire studies; Electronic commerce